Gambaran Lifestyle Behavior, Strategi Koping dan Subjective Well-being Remaja Selama Pandemi Covid-19 di Kota Banda Aceh - Hidayati, Rahma; Asniar, Asniar; Rachmalia, Rachmalia (Holistic Nursing and Health Science, 2023)
Introduction: Adaptation to new situations caused by the Covid-19 pandemic limits adolescents' spaces in performing daily routines. This limitation also impacts their subjective well-being. Subjective well-being relates to lifestyle behavior and coping strategies. Therefore it is essential to assess in defining appropriate nursing interventions for adolescents. This study aimed to describe lifestyle behavior, coping strategies, and subjective well-being during the Covid-19 pandemic in Banda Aceh City. Methods: This study employed a descriptive exploratory design with a cross-sectional approach, involving 168 adolescents selected by snowball sampling. Data was collected by using a self-report questionnaire distributed by google form.Results: The study findings show that most of the adolescents tried to obey the regulations during the Covid-19 pandemic (63.1%); few of the respondents planned their daily routines (19.0%); were involved in different activities (10.7%), and only a few who do physical activity regularly (21.4%). Adolescents often shared their feelings (31.5%) and reviewed their relationships with their families (38.7-42.3%). In terms of social and school interactions, adolescents maintained contact with their friends and teachers (35.1-43.5%). The adolescents maintained school obligations at home (49.4%),  and this period did not affect their educational path (50.0%). In addition, most adolescents reported slight changes in subjective well-being (41.1%) and mild anxiety (38.1%). Discussion/Suggestion: This study highlights several conditions that need consideration from relevant stakeholders, including community health nurses or school health nurses, in designing interventions to prevent poor lifestyle behaviors and improve adolescents' adaptive coping and subjective well-being. Consequently, nurses should collaborate with families, school boards, public health centers, district health offices, and other government sectors in implementing health promotion programs for adolescents during the Covid-19 pandemic, particularly in improving lifestyle behaviors, adaptive coping, and subjective well-being.